Catastrophic conditions in couple systems - Lynch, Barbara J (Journal of Couples Therapy, 1999)
A presentation of case studies forms the focus for an exploration of the discovery of an abortion or adoption used as the management of an unwelcome pregnancy which occurred in the context of the marital system. Managing an impasse in the middle phase of therapy in each case led to the emergence of information which then allowed the therapist to work with the couple system to alleviate the core situation out of which presenting problems emanated. In these cases the unwelcome pregnancy had the potential to be cataclysmic to the couple system. Therefore, the possibility that a couple is concealing an abortion or an adoption should be considered by couples' therapists when there is little or no response to usual strategies for change. The reason for concealment is immaterial. What is paramount is that the therapist bring the event to the fore of treatment and work with a couple to put closure on what is generally an unresolved issue. © 1999, by The Haworth Press, Inc. All rights reserved.
Keywords: Abortion; Adoption; Grief; Pregnancy; dept.mft

Partnership and ego equality in the marital system - Lynch, Barbara J (Journal of Couples Therapy, 1992)
Keywords: dept.mft

A structural family therapist responds to "A feminist critique of organizational humanism": - Lynch, Barbara J (The Journal of Applied Behavioral Science, 1994)
Keywords: dept.mft

An anatomy of bonding in the dyadic system - Lynch, Barbara J. (Journal of Couples Therapy, 1991)
Bonding is an essential factor in the establishment and maintenance of an intimate committed relationship. Dissecting elements of bonding leads to an understanding of the internal structure of the marriage. Attraction and bonding are different and equally vital in turning initial romance into enduring intimacy. The process of attraction based on projections developing into an enduring bond between peers merges relationship purpose and a rationale for emotional involvement. This occurs when attention is accorded to each of the factors of bonding; ego-equality, respect, interdependence and reality grounding. In therapy, a couple’s bonding can be assessed through the isomorphic qualities actualized in the therapeutic joining process. Discussions includes over bonded and under bonded couples, their presenting problems, and a treatment focus for each condition. © 1991 Taylor & Francis Group, LLC.
Keywords: dept.mft

Responses to carlotta regan tyler - Calvert, Linda Mcgee; Ramsey, V Jean; Alderfer, Charleen; Lynch, Barbara J (The Journal of Applied Behavioral Science, 1995)
Keywords: dept.mft